Pemberdayaan Siswa MA NW Sepit melalui Pelatihan Desain Grafis Menggunakan Canva dan Editing Video Sederhana untuk Mendukung Literasi Digital - Zul Hidayatullah; Nuraini; Nunung Ariandani; Muhammad Qusyairi (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The development of digital technology requires students to have adequate digital literacy skills to face the challenges of the 21st century. However, many students still use technology only for entertainment and lack productive digital skills. This community service activity aims to improve the digital literacy of MA NW Sepit students through graphic design training using Canva and simple video editing. The implementation method uses a participatory approach that actively involves students in the entire series of activities, from material delivery, demonstrations, hands-on practice, to mentoring. The training was conducted over three days with a focus on introducing Canva, creating visual designs, and the basics of video editing to produce creative and educational digital content. The results of the activity showed an increase in students' knowledge and skills in utilizing digital technology productively. Participants were able to use Canva's features to create posters, pamphlets, presentations, and other visual content, as well as understanding basic video editing techniques. In addition to improving technical skills, this activity also increased students' creativity, confidence, and motivation in producing digital works. The high enthusiasm and participation of participants during the training are indicators of the program's success. This activity demonstrates that graphic design and video editing training can be an effective strategy in supporting the strengthening of students' digital literacy in the school environment.